PENERAPAN MODEL QUANTUM TEACHING BERBASIS TEORI TRIKON UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI KERAGAMAN SUKU BANGSA DAN BUDAYA DI INDONESIA - Nitidisastra, Tri Sulistio; Hanifah, Nurdinah; Sunarya, Dede Tatang (Jurnal Pena Ilmiah, 2017)
This research is based on learning in the material of ethnic and cultural diversity in Indonesia which is less interesting for students, because it is too broad discussion, also limitation of innovation in its delivery. This problem occurs in class V SDN 1 Budur Ciwaringin Sub-district of Cirebon Regency, at the time of initial data collection there is only 1 student whose value exceeds or equal to KKM, and there are 30 students whose value is less than KKM. The purpose of this study is obtaining an overview of the increasing student learning outcomes in social studies materials ethnic and cultural diversity in Indonesia through the application of learning models of Quantum Teaching based on the theory Trikon. This research uses Classroom Action Research method which is implemented in three cycles. Based on the data obtained showed that the learning outcomes of students after learning model of Quantum Teaching based on the theory Trikon continues to increase, with an average increase of 30.44%. Of the three cycles.